Organically surface engineered mesoporous silica nanoparticles control the release of quercetin by pH stimuli - Saputra, Ozi Adi; Lestari, Windy Ayu; Kurniansyah, Viardi; Lestari, Witri Wahyu; Sugiura, Takashi; Mukti, Rino R.; Martien, Ronny; Wibowo, Fajar Rakhman (Nature Research, 2022)
Controlling the premature release of hydrophobic drugs like quercetin over physiological conditions remains a challenge motivating the development of smart and responsive drug carriers in recent years. This present work reported a surface modification of mesoporous silica nanoparticles (MSN) by a functional compound having both amines (as a positively charged group) and carboxylic (negatively charged group), namely 4-((2-aminoethyl)amino)-4-oxobut-2-enoic acid (AmEA) prepared via simple mechanochemistry approach. The impact of MSN surface modification on physical, textural, and morphological features was evaluated by TGA, N2 adsorption–desorption, PSA-zeta, SEM, and TEM. The BET surface area of AmEA-modified MSN (MSN-AmEA) was found to be 858.41 m2 g−1 with a pore size of 2.69 nm which could accommodate a high concentration of quercetin 118 higher than MSN. In addition, the colloidal stability of MSN-AmEA was greatly improved as indicated by high zeta potential especially at pH 4 compared to MSN. In contrast to MSN, MSN-AmEA has better in controlling quercetin release triggered by pH, thanks to the presence of the functional groups that have a pose-sensitive interaction hence it may fully control the quercetin release, as elaborated by the DFT study. Therefore, the controlled release of quercetin over MSN-AmEA verified its capability of acting as a smart drug delivery system. © 2022, The Author(s).